Heyde’s syndrome as a rare cause of gastrointestinal bleeding in aortic stenosis patients - D. V. Belov; D. V. Garbuzenko; O. P. Lukin; S. S. Anufrieva (Кардиоваскулярная терапия и профилактика, 2021)
Heyde’s syndrome is one of the causes of gastrointestinal bleeding in patients with heart disease. It is characterized by the acquired destruction of high molecular weight multimers of von Willebrand factor due to high hydraulic shear stress on the aortic valve in severe stenosis, followed by gastrointestinal bleeding due to angiodysplasias. Management of such patients is a complex and relevant problem. The central method of treatment for Heyde’s syndrome is aortic valve replacement, which reduces the risk of recurrent gastrointestinal bleeding in more than 90% of patients.